Environmental Risks in the Safety Assurance System - VLADIMIROVNA EFANOVA, Elena; VASILIEVICH MAKLACHKOV, Alexander (Journal of Environmental Management and Tourism; Vol 6 No 1 (2015): JEMT Volume VI Issue 1(11) Summer 2015, 2016)
National safety has a political, socio-cultural, and economic determination. Ecological determination becomes meaningful in the context of the redistribution of the world's natural resources and comprehension of the environmental conditions and sustainable development challenges. But how we can link environmental problems and safety? It is obvious that we need a multi-disciplinary approach, analyzing the relationship between the environment and the problem of human security. We are talking about the need for research to develop a new paradigm of general civilization movements, which does not contradict the national interests of countries at different levels of development.
Keywords: safety, environmental risk, ecological safety, policy